PENGARUH PERBESARAN LUAS ELEKTRODA TERHADAP PROBABILITAS TEGANGAN TEMBUS PADA DIELEKTRIK MINYAK MENGGUNAKAN SUMBER TEGANGAN TINGGI AC - Latif, Nabila Fauziah; Dhofir, Moch.; Hasanah, Rini Nur (Jurnal Mahasiswa TEUB, 2024)
Failure of the insulation system in electrical equipment results in breakdown voltage which can occur in a gas dielectric in theform of air or a liquid dielectric in the form of oil. The breakdown voltage that occurs in transformer oil is due to the presenceof contaminants between the two conductors that bridge the space between the two conductors imperfectly. Transformers havedifferent sizes depending on the maximum power that can be handle. The phenomenon of differences in conductor dimensionsin transformers that have different sizes is likened to electrodes with different cross-sectional area dimensions. The differencein conductor dimensions can affect the distribution of the surrounding electric field which affects the probability of breakdownvoltage. This research will describe the effect of electrode area enlargement on the probability of breakdown voltage in oildielectric using AC (Alternating Current) high voltage source. The research method used is by taking data directly conductedat the High Voltage and Application Laboratory of the Department of Electrical Engineering, Faculty of Engineering, Universitas Brawijaya. Simulation of electric field distribution was carried out using FEMM 4.2 software. The variation of cross-sectional area of the electrode rod arrangement used is A, 2A, 3A, 4A, and 5A. The data taken includes the value of oil conductivity, leakage current, and breakdown voltage. Measurement of oil conductivity using a high voltage insulation tester with output in the form of oil resistance value. Measurement of leakage current value is carried out using a test voltage variation of 2 kV, 4 kV, and 6 kV. The breakdown voltage test was carried out using the Up and Down method in 26 trials and analyzed the probability of breakdown based on the Normal Distribution (Gaussian) graph. The results obtained from this study are the greater the electrode area, the more even/homogeneous the electric field distribution, the greater the leakage current value so that the oil resistance between the electrodes is getting smaller, the larger the electrode area, the smaller the breakdown voltage value and the greater the probability of breakdown. Keywords: Shell Diala oil B, rod electrode, leakage current, probability, breakdown voltage